Antibiotic Prophylaxis in Clean-Contaminated Head and Neck Surgery: A Systematic Review and Meta-analysis. (October 2017) - Vila, Peter M.; Zenga, Joseph; Fowler, Susan; Jackson, Ryan S.
Objective: To determine the optimal duration and type of antibiotic prophylaxis in patients undergoing clean-contaminated resection for head and neck cancer. Data Sources: Search strategies were created by a medical librarian, implemented in multiple databases, and completed in June 2016. Review Methods: The population of interest was adults ≥18 years undergoing clean-contaminated head and neck surgery, intervention was postoperative antibiotic prophylaxis, comparator was duration and types of antibiotics used, outcome was the wound infection rate, and the study design was randomized controlled trials (RCTs). Studies were excluded if not randomized, did not use systemic antibiotics, did not study wound infections, or included children. After excluding duplicates, the search strategy yielded 427 abstracts. After applying inclusion and exclusion criteria, 67 studies were screened, leaving 19 RCTs for review. PRISMA guidelines were followed. A random-effects model was used for meta-analysis. Results: Meta-analysis of 340 patients in 4 RCTs showed that the pooled relative risk of wound infection was 0.98 (95% confidence interval [CI], 0.58-1.61; P = .718; I 2 = 0.0%) in patients receiving 1 day vs 5 days of prophylaxis. Conclusion: This study provides evidence that there is no difference in the risk of wound infection with 1 day vs 5 days of systemic antibiotic prophylaxis in clean-contaminated head and neck surgery, consistent with existing guidelines. Future large randomized trials are needed to more clearly define the appropriate choice of prophylaxis in penicillin-allergic patients.